Adaptive Strategy of Community Service in Improving HR Digital Resilience through Transformation of Online Marketing Techniques - Kraugusteeliana, Kraugusteeliana; Muhamad, Lili Fadli; Junaidi, Ahmad (PT. LITERASI SAINS NUSANTARA, 2025)
The accelerating digital transformation demands the readiness of human resources (HR), especially in the aspect of online marketing, as a strategy to survive and thrive in the digital economy era. This research aims to examine how adaptive strategies in community service activities can be used to improve HR digital resilience through an online marketing technique transformation approach. Using a qualitative literature review method and descriptive analysis, data were obtained from 30 scientific articles and credible sources published in the period 2000-2024, and after a rigorous selection process, 18 articles were used as the basis for analysis. The results showed that an adaptive strategy involving community empowerment, technology integration, and digital marketing training based on local needs, proved effective in improving the digital capacity of the community. Support from the theories of Community Empowerment, Diffusion of Innovations, and Resilience Thinking reinforce that participatory and contextual approaches in community service can encourage community resilience and digital innovation. Case studies from various regions in Indonesia also show the success of online marketing techniques training in improving the digital presence and economic sustainability of local communities. These findings provide an important contribution to the development of community service strategies that are more relevant to the demands of community-based digital transformation.